Interstellar Scintillation and Scattering of Micro-arc-second AGN - Jauncey, D.; Bignall, H.; Kedziora-Chudczer, L.; Koay, J.; Lovell, J.; Macquart, Jean-Pierre; Ojha, R.; Pursimo, T.; Reynolds, C.; Rickett, B. (MDPI AG, 2016)
The discovery of the first quasar 3C 273 led directly to the discovery of their variability at optical and radio wavelengths. We review the radio variability observations, in particular the variability found at frequencies below 1 GHz, as well as those exhibiting intra-day variability (IDV) at cm wavelengths. Observations have shown that IDV arises principally from scintillation caused by scattering in the ionized interstellar medium of our Galaxy. The sensitivity of interstellar scintillation towards source angular sizes has provided a powerful tool for studying the most compact components of radio-loud AGN at microarcsecond and milliarcsecond scale resolution.